Follicular T-cell subsets in HIV infection: recent advances in pathogenesis research. Issue 2 (March 2019) - Xu, Yin; Ollerton, Matthew T.; Connick, Elizabeth
Abstract : Purpose of review: T cells within B-cell follicles of secondary lymphoid tissues play key roles in HIV immunopathogenesis. This review highlights recent findings and identifies gaps in current knowledge. Recent findings: B-cell follicles are major sites of virus replication and demonstrate significant impairments in the generation of humoral immunity in HIV infection. Follicular T helper cells (Tfh), follicular T regulatory cells (Tfr) and follicular CD8 + T cells (fCD8) play key roles in HIV immunopathogenesis. Tfh and more recently Tfr are highly permissive to HIV, and may serve as reservoirs of HIV in treated infection. Virus-specific CD8 + T cells are less abundant in B-cell follicles than extrafollicular regions, but their effector mechanisms remain an area of significant controversy. Impairments in Tfh likely contribute to impaired humoral immunity and potential mechanisms include B-cell counter-regulatory mechanisms, Tfr suppression and diminished repertoire breadth. A better understanding of the roles of Tfh, Tfr and fCD8 in HIV immunopathogenesis is critical to the development of effective HIV vaccines and cure strategies. Summary: Tfh, Tfr and fCD8 contribute to HIV persistence and impaired humoral immunity. A better understanding of their roles could facilitate vaccine development and HIV cure strategies.